Macro-moth fauna ( lepidoptera: heterocera) of Tasik Chini, Pahang Malaysia. - Norela Sulaiman,; Azman Sulaiman,; Zaidi Md Isa,; Maimon Abdullah,; Muhamad Azizi Jazmi, (Pusat Sistematik Serangga ,UKM, 2011)
A Study on aesthetic insects (macro-moth fauna) was conducted at three different locations of Tsik Chini area in Pahang , Malaysia The three locations were the base camp (site A) an abandoned mine (site B) and kampung melai (site c) Sampling were conducted from 22-26 may 2004 and from 22-24 july 2004 using a light-trap (9illuminated by a 160-watt mercury vapour buld). A total of 176 species has been recorded, comprising 106 species (310 individuals) from location B and 28 species (210 individuals)from location c, respectively. This total encompassed 19 families, geometridae (67 species),noctuidae (38 species), arctiidae (17 species),sphingidae(9 species),notodontidae (8 species),Lymantriidae (8 species), Lasiocampidae (7 species), limacodidae (5 species) drepanidae( species),uraniidae, bombycidae saturniidae(two species each),chalcosiidae, nolidae, agaristidae, cossidae, cyclidiidae, and epiplemidae) one species each). All of the 176 species recorded in this study are preliminary records since there no previous publication of moth from Tasik Chini, Pahang. The Shannons diversity index (H') for location A(H'=4.23)was significantly higher(p<0.05)that than of location B (H'=3.71 or location C (H'=2.01))respectively. In terms of the cumulative value for species diversity of moths(H') the study found thar seven sampling occasions were still insufficient for location A, six samplings were minimally sufficient for location B and two samplings were minimally sufficient for location C. Percentages of overlapping species were all low between A and B (22.62%),B and C (15.74%) and A and C (12.5%) respectively .A total of 12 species were found to be common spatially (i.e found in all three locations). Among all thespecies, Hypochrosis binexata walker(geometridae) was found to be the nost common spatially as well as temporary ( i.e found on every sampling occasion, with an overall total of 180 individuals) some 79 species appeared rare, each represented by only one individual throughout the study period.